Kinetics Studies for the Adsorption of b-Carotene on Mesoporous Carbon Coated Monolith: Effect of Concentration and Temperature - Ali Khan, Moonis; S.Y. Choong, Thomas; T.G. Chuah, Luqman; Yunus, Robiah; Y.H. Yap, Taufiq; Muhammad (Asian Journal of Chemistry, 2012)
The adsorption kinetics for the removal of b-carotene as functions of temperature and initial b-carotene concentration onto mesoporous carbon coated monolith in isopropyl alcohol and n-hexane solutions was investigated. The adsorption capacity increased as initial b-carotene concentration and temperature increased. Two kinetic models, pseudo-first-order and pseudo-second-order, were used to describe the adsorption kinetics. To identify the adsorption mechanism rate parameters for intraparticle diffusion model were evaluated. The results showed that the adsorption of b-carotene onto mesoporous carbon coated monolith followed pseudofirst- order model in isopropyl alcohol solution and pseudo-second-order model in n-hexane solution. The activation energies were 11.45 and 9.41 kJ/mol in isopropyl alcohol and n-hexane solutions, respectively.